Early Modern Aristotle : On the Making and Unmaking of Authority - Del Soldato, Eva (University of Pennsylvania Press, 2020)
Cover -- Early Modern Aristotle -- Title -- Copyright -- CONTENTS -- Chronology -- Introduction -- Chapter 1. Comparing Philosophers: How to Elevate or Undermine an Authority -- Chapter 2. Comparationes and External Aids -- Chapter 3. Learning, Protecting, Advertising: Comparationes in University Halls -- Chapter 4. Customizing Authorities: Legends, Anecdotes, Fictions -- Chapter 5. If Aristotle Were Alive, or the Paradoxes of Authority -- Epilogue -- Appendix A. Preface by Alfonso Pandolfi to His Comparatio -- Appendix B. Federico Pendasio's Comparatio -- Appendix C. Skeptical Attitudes Toward Philosophical Concordiae -- Appendix D. Francesco Vimercato's De Dogmatibus -- Notes -- Bibliography -- Index -- Acknowledgments.